Analysis of Bed Availability and COVID-19 Deaths Relationship in Jakarta - Refina Muthia Sundari; Dartanto, Teguh; Dharmawan, Goldy F. (Universitas Negeri Semarang, 2024)
The surge in COVID-19 cases that hit Indonesia in May – July 2021 led to a decline in the capacity of the health system. It was reflected by an increase in the national Bed Occupancy Ratio (BOR) percentage of more than 60%, where DKI Jakarta had the highest percentage of BOR among all provinces, reaching 85%. The death rate also soared at 256 deaths per day. The government responded this incident by continuing to increase the bed capacity, so BOR percentage could be decreased in order to preventing a higher death rate. Therefore, this study was conducted to analyze how the impact of increasing bed capacity on deaths from COVID-19. This study estimates 511 time series data using the Ordinary Least Square (OLS) method. As a result, the addition bed capacity had a negative association with COVID-19 deaths. The increase in overall bed capacity, ICU bed capacity, and isolation bed capacity could reduce deaths of COVID-19 by 22.5%, 17.3% and 22.7%, respectively.